2021
DOI: 10.1186/s12985-021-01521-3
|View full text |Cite
|
Sign up to set email alerts
|

Caveolin-1 is involved in encephalomyocarditis virus replication in BHK-21 cells

Abstract: Background Encephalomyocarditis virus, member of Cardiovirus genus within Picornaviridae family, is an important pathogen that infects different domestic and wild animals. However, the molecular mechanism of its entry remains unclear. In this study, we investigated the mechanism of EMCV infectivity in relation to endocytic pathway using BHK-21 cells. Methods The function of numerous cellular key factors implicated in the various endocytic mechanism… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 74 publications
(50 reference statements)
0
4
0
Order By: Relevance
“…During virus entry via macropinocytosis, the formation of membrane ruffles depends on actin rearrangement, p21-activated kinase 1 (Pak1) is a member of the PAK family and promotes actin rearrangement ( Han et al, 2016 ). To further determine the dependence of BRSV entry into MDBK cells on macropinocytosis, we treated MDBK cells with the Pak1 inhibitor, IPA-3 ( Li et al, 2021 ). The result of cell viability showed that IPA-3 greater than 15 μM inhibited the viability of MDBK cells ( Figure 5E ).…”
Section: Resultsmentioning
confidence: 99%
“…During virus entry via macropinocytosis, the formation of membrane ruffles depends on actin rearrangement, p21-activated kinase 1 (Pak1) is a member of the PAK family and promotes actin rearrangement ( Han et al, 2016 ). To further determine the dependence of BRSV entry into MDBK cells on macropinocytosis, we treated MDBK cells with the Pak1 inhibitor, IPA-3 ( Li et al, 2021 ). The result of cell viability showed that IPA-3 greater than 15 μM inhibited the viability of MDBK cells ( Figure 5E ).…”
Section: Resultsmentioning
confidence: 99%
“… 41 , 42 Lastly, viral entry and replication pathways were examined, and data indicated downregulation in several genes that have been associated with the entry and replication of many viruses ( Figure 6 E) (TRIM25, cav1, oas2, oasl1, dicer1, and PTX3). 43 , 44 , 45 , 46 , 47 , 48 We also compared the basal gene expression of these pathways in untreated WT and CD11c-dnRARα BMDCs ( Figure S8 ). We found, in comparison to WT, CD11c-dnRARα DCs have higher expression of genes related to innate and adaptive pathways while inflammatory pathway was overall down.…”
Section: Resultsmentioning
confidence: 99%
“…A previous study had shown that EMCV infection is associated with the caveolar/lipid raft-dependent endocytic pathway [18]. In addition, both Rab5 and Rab7 are required for endocytosis.…”
Section: Ifitm Proteins Enhanced Ifn-β Production During Emcv Infectionmentioning
confidence: 97%